2021
DOI: 10.25159/1016-8427/6308
|View full text |Cite
|
Sign up to set email alerts
|

Hermeneutic Analysis: Making Sense of Symbolic Expressions in Izibongo of King Shaka

Abstract: A substantial number of scholars have previously documented African praise poems, including those that relate to the Zulu kings and queens. To a large extent, these recordings only focus on the content and structural approach to this genre of orality, with little attention paid to contextual meaning.  As such, issues of metaphoric expressions are perpetually ignored, which by their very definition contain the underlying meaning and purpose for the crafting of such poetry. Therefore, this article addresses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Consistent with the previous studies (Kloppers 2020;Ngema 2020), the findings of this study reveal that singing an incomplete hymn eradicates the original meaning and purpose of the hymn. The researcher found that although contemporary gospel musicians are inspired by Zulu traditional hymns iCilongo Levangeli, the musicians must examine the context to understand the hymns.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the previous studies (Kloppers 2020;Ngema 2020), the findings of this study reveal that singing an incomplete hymn eradicates the original meaning and purpose of the hymn. The researcher found that although contemporary gospel musicians are inspired by Zulu traditional hymns iCilongo Levangeli, the musicians must examine the context to understand the hymns.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, these three Zulu traditional hymns are misinterpreted and misunderstood by contemporary gospel musicians as they do not sing them completely. The issue of misinterpreting and misunderstanding Zulu traditional hymns is partly attributable to the original contemporary musicians' ignorance of the underlying true meaning, emotions, state and purpose (Ngema 2020;Thebe 2020).…”
Section: Ngisho Nayo Ingelosimentioning
confidence: 99%
See 1 more Smart Citation